A hyperbolic-type azimuthal velocity model for equatorial currents. Issue 3 (11th February 2022) - Marynets, Kateryna
ABSTRACT: We discuss a mathematical model for the equatorial current across the Pacific Ocean, obtained as a leading-order solution to the Navier-Stokes governing equations for geophysical flows in a rotating frame.